If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7.5(2y + 4) + -2.9(3y + -6) = 0 Reorder the terms: -7.5(4 + 2y) + -2.9(3y + -6) = 0 (4 * -7.5 + 2y * -7.5) + -2.9(3y + -6) = 0 (-30 + -15y) + -2.9(3y + -6) = 0 Reorder the terms: -30 + -15y + -2.9(-6 + 3y) = 0 -30 + -15y + (-6 * -2.9 + 3y * -2.9) = 0 -30 + -15y + (17.4 + -8.7y) = 0 Reorder the terms: -30 + 17.4 + -15y + -8.7y = 0 Combine like terms: -30 + 17.4 = -12.6 -12.6 + -15y + -8.7y = 0 Combine like terms: -15y + -8.7y = -23.7y -12.6 + -23.7y = 0 Solving -12.6 + -23.7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12.6' to each side of the equation. -12.6 + 12.6 + -23.7y = 0 + 12.6 Combine like terms: -12.6 + 12.6 = 0.0 0.0 + -23.7y = 0 + 12.6 -23.7y = 0 + 12.6 Combine like terms: 0 + 12.6 = 12.6 -23.7y = 12.6 Divide each side by '-23.7'. y = -0.5316455696 Simplifying y = -0.5316455696
| 2x+x=145 | | x+.625=.25 | | 33x^2-12x+5x=0 | | 3.4x=2.6x+4.0 | | 0.80x+0.50(2-x)=0.10(-74) | | 9=-63v+(-54) | | 5j+5=t-2 | | 7x-9+6x=(-126) | | x-27=-16 | | 3x+8-2x=15 | | t-6+1=3 | | 6x-5(3+2x)=1 | | 4-7*1=39 | | -4(-3k+3)-(6k-4)-2k+1= | | 2(2x+b)=16 | | -75=-21n-(-9) | | 28x^2-52x+28=4x^2 | | 28x^2-52x+28=4m^2 | | 2(9-6x)-49=5 | | 6x^2=4x+30 | | 3*4-13=8 | | 22=19+x | | -16b=4 | | 2x^2+12x=-35-7x | | 75=3(-6n-6) | | 3x+8.3= | | 24x^2+144x+28=4x^2 | | -2(-3k+2)+-(5k+-6)+-3k+-5= | | 4.3x-7.9x=-18 | | 8x-3(x+9)=4x+12 | | 6x^2-19x+27=3+4x^2 | | -2(-3k+2)+-1(5k+-6)+-3k+-5= |